Проблемы пробуждения коммунизма и халифата как форма чёрной кампании на президентских выборах в Индонезии в 2019 году (Issues of the Awakening of Communism and Khilafah as a Form of a Black Campaign in the Presidential Election in Indonesia in 2019) - Zahrotunnimah Zahrotunnimah; Ida Susilowati (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractThe 2019 presidential election has a different political nuance compared to previous elections in Indonesia. Increased political participation in society gave birth to militant political volunteers in each of the paslon camps. As political participation increases, it is undeniable that there are also indications of a black campaign in the 2019 presidential election contestation this year. The issue of communism and the issue of khilafah are examples of the existence of a black campaign that threatens the democratization of elections in Indonesia and even threatens the disintegration of the nation. The following article seeks to find out how black campaigns can develop in Indonesia and the efforts of the government and the community in counteracting black campaigns in elections in Indonesia. Actualization of Pancasila values in the form of legislation was made by the government as an effort to cope with the hoax news circulation. The internationalization of the values of Pancasila in people's lives has an important role as a solution to face the black campaign in the process of democratic political socialization. This is an effort to realize the creation of social justice for all the people of Indonesia, through the realization of a rigorous election.Keywords: Black campaign, communism, Islamic caliphate, political socialization, election democratizationAbstrak Pemilu presiden 2019 memiliki nuansa politik yang berbeda dibanding pemilu-pemilu yang pernah terjadi sebelumnya di Indonesia. Meningkatnya partisipasi politik di masyarakat melahirkan relawan politik yang militan di masing-masing kubu paslon. Seiring meningkatnya partisipasi politik tersebut, tidak dapat dipungkiri meningkat pula indikasi adanya black campaign dalam kontestasi pilpres 2019 tahun ini. Isu komunisme dan isu khilafah menjadi salah satu contoh wujud dari adanya black campaign yang mengancam demokratisasi pemilu di Indonesia bahkan mengancam dis-integrasi bangsa. Artikel berikut berusaha untuk mencari tahu bagaimana black campaign dapat berkembang di Indonesia dan upaya pemerintah serta masyarakat dalam menangkal black campaign pada pemilu di Indonesia. Aktualisasi nilai-nilai Pancasila dalam bentuk perundang-undangan dibuat pemerintah sebagai upaya menanggulangi beredarnya berita hoax. Internasilasi nilai-nilai Pancasila dalam kehidupan masyarakat memiliki peranan cukup penting sebagai solusi menghadapi black campaign dalam proses sosialisasi politik yang demokratis. Hal tersebut sebagai upaya mewujudkan terciptanya keadilan sosial bagi seluruh rakyat Indonesia, melalui realisasi pemilu yang luberjurdil. Kata kunci: Black campaign, komunisme, khilafah islam, sosialisasi politik, demokratisasi pemiluAннотация Президентские выборы 2019 года имеют свои политические особенности по сравнению с предыдущими выборами в Индонезии. Увеличение политического участия в обществe привело к появлению воинствующих политических добровольцев в каждом из оплотов кандидатов. Поскольку участие в политической сфере возрастает, нельзя отрицать, что возрастает также количество приёмов черной кампании в президентских выборах в этом году. Проблемы коммунизма и халифата являются примерами существования черной кампании, которая угрожает не только демократизации выборов в Индонезии, но и национальной интеграции в целом. В статье рассматриваются пути использования чёрной кампании в Индонезии и существующие государственные и общественные меры по противодействию черной кампании на выборах в Индонезии. Принятие ценностей Панчасилы (пять принципов, лежащих в основе индонезийской модели построения общества “справедливости и процветания”) в форме законодательства было осуществлено правительством для борьбы с распространением ложных новостей. Интернализация ценностей Панчасилы в жизни общества играет важную роль в качестве решения противостоять черной кампании в процессе демократической политической социализации. Это попытка реализовать создание социальной справедливости для всех жителей Индонезии путем осуществления выборов “Luberjurdil” (прямых, публичных, свободных, конфиденциальных, честных и справедливых). Ключевые слова: чёрная кампания, коммунизм, исламский халифат, политическая социализация, демократизация выборов